Nondecalcified histologic study of bone response to titanium implants topographically modified by laser with and without hydroxyapatite coating - Sisti, Karin E.; Piattelli, Adriano; Guastaldi, Antonio C. [UNESP]; Queiroz, Thallita P.; De Rossi, Rafael (My University, 2013)
The purpose of this study was nondecalcified histologic analysis of titanium implants modified by laser with and without hydroxyapatite. Implants with three modified surfaces were inserted into rabbit tibias: group 1, machined surface; group 2, irradiated (laser); and group 3, irradiated and hydroxyapatite coated (biomimetic method). The mean surface roughness (Ra) scores of groups 2 and 3 were higher than that of group 1. Boneimplant contact measurements at 30 and 60 days for groups 2 and 3 were higher than for group 1. Bone area at 30 and 60 days for group 2 was higher than for groups 1 and 3. Titanium implants modified by laser with and without hydroxyapatite exhibit increased early osseointegration. © 2013 by Quintessence Publishing Co Inc.